The tribological and electrochemical behavior of HVOF-sprayed Cr3C2–NiCr ceramic coating on carbon steel - Zavareh, M.A.; Sarhan, A.A.D.; Bushroa, Abdul Razak; Basirun, Wan Jefrey (Elsevier, 2015)
High Velocity Oxygen Fuel (HVOF) is an excellent approach to prepare a good, wear-resistant lamella of Chromium Carbide-Nickel Chrome (Cr3C2-NiCr) on carbon steel for high temperature application. This research investigates the effect of a thin, deposited layer of Cr3C2-NiCr on carbon steel in terms of wear and corrosion properties. The microstructure of the HVOF-sprayed Cr3C2-NiCr coating was characterized at each step by scanning electron microscopy. Wear testing was performed with a pin-on-disk tester. Wear weight loss was examined by applying different loads over a 9048.96 m sliding distance. Experimental results show that the wear resistance of the coated sample reduced the risk of seizure compared to the uncoated sample. An electrochemical test was also performed and the behavior of the substrate in the coated sample was investigated in 3.5 NaCl for 27 days. Electrochemical Impedance Spectroscopy (EIS) showed that the HVOF coating has high corrosion resistance and protects the substrate from NaCl electrolyte penetration. So deposition this layer of ceramic composite is protected oil piping from synergistic attack of seawater during the transport of crude oil to the refinery. (C) 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.